2007
DOI: 10.1097/01.coc.0000256691.27796.24
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Involved-Field Irradiation Versus Elective Nodal Irradiation in Combination With Concurrent Chemotherapy for Inoperable Stage III Nonsmall Cell Lung Cancer

Abstract: IFI arm achieved better overall response and local control than ENI arm, and it allowed a dose of 68 to 74 Gy to be safely administered to patients with inoperable stage III NSCLC. Outcome improvement can be expected by conformal IFI combined with chemotherapy for stage III NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(105 citation statements)
references
References 16 publications
0
101
0
Order By: Relevance
“…Yuan et al (29) reported a prospectively randomised dose escalation trial in patients with inoperable stage III NSCLC who were enrolled on 3DCRT of 1.8 to 2 Gy and 68 to 74 Gy for involved-field irradiation (IFI) covering the primary tumour and involved lymph nodes, or 60 to 64 Gy covering the primary tumour and involved lymph nodes, and elective nodal irradiation (ENI). Yuan et al (29) documented a better outcome and local control, as well as lower radiation pneumonitis rates, in the dose escalated (68-74 Gy) IFI arm than the 60 Gy ENI arm.…”
Section: Significance Of Dose Escalation In Locally Advanced Nsclcmentioning
confidence: 98%
“…Yuan et al (29) reported a prospectively randomised dose escalation trial in patients with inoperable stage III NSCLC who were enrolled on 3DCRT of 1.8 to 2 Gy and 68 to 74 Gy for involved-field irradiation (IFI) covering the primary tumour and involved lymph nodes, or 60 to 64 Gy covering the primary tumour and involved lymph nodes, and elective nodal irradiation (ENI). Yuan et al (29) documented a better outcome and local control, as well as lower radiation pneumonitis rates, in the dose escalated (68-74 Gy) IFI arm than the 60 Gy ENI arm.…”
Section: Significance Of Dose Escalation In Locally Advanced Nsclcmentioning
confidence: 98%
“…[105][106][107] With tantalizing recent data suggesting that radiotherapy parameters, such as dose and fractionation, may be of significance in altering survival, either alone or in combination with chemotherapy, dose-escalation trials have been pursued, with promising clinical results. [108][109][110][111] However, conventional dose escalation has not provided clear evidence of benefit in the recently terminated Radiation Therapy Oncology Group (RTOG) trial that evaluated 74 versus 60 Gy dosages of therapy.…”
Section: Unresectable Diseasementioning
confidence: 99%
“…In the only prospective study comparing ENI with IF-RT, Yuan et al evaluated the effects of IF-RT in their prospective randomized trial in which 193 patients were randomly assigned to IF-RT to 68 to 74Gy or ENI to 60 to 64Gy using 3D-CRT, and reported that ENF was found in only 4% of patients in the ENI arm versus 7% in the IF-RT arm within 5 years 19) . Although the irradiation dose to elective nodal regions was higher in the ENI arm than in IF-RT arm, ENF was not significant in either arm (p=0.351).…”
Section: The Evidence Of If-rt -Is Eni Needed?mentioning
confidence: 99%